Design and Implementation of an Online Food Ordering System Using the Agile Scrum - Saniyyah Wafa Nurjihan; Nafis Faturrahman; Nurbadillah; Indra Maki Wiguna; Aditya Wicaksono; Muhammad Nasir (PPM Telkom University, 2025)
Food4U is a web-based online food ordering platform designed to improve restaurant service efficiency through QR code scanning. The system was created following the Agile Scrum approach, which supports a flexible and iterative development process tailored to the needs of users. The project progressed through multiple sprints, which included analyzing requirements, designing the system, implementing essential functionalities, and conducting testing through the black-box method. Test results show that most features, including user login, menu browsing, order placement, and admin transaction management, are working effectively, achieving a success rate of over 85%. The implementation of the Agile Scrum approach has been successful in speeding up the development process while maintaining system quality that meets user standards. The system still has opportunities for further improvements, such as adding digital payment options and analytical tools for restaurant operators.